Anti-HLA antibodies bound to monocytes altered antibody-mediated platelet phagocytosis and led to mild thrombocytopenia - Xu, Xiuzhang; Baal, Nelli; Rick, Martin; Chen, Dawei; Liang, Huaqin; Ye, Xin; Xia, Wenjie; Ren, Hui; Xu, Yaori; Fu, Yongshui; Bein, Gregor; Santoso, Sentot (Frontiers in Immunology, 2025)
BackgroundIn fetal and neonatal alloimmune thrombocytopenia (FNAIT), maternal antibodies react with alloantigen expressed on fetal platelets, leading to their clearance via antibody-dependent phagocytosis. In Caucasians, most FNAIT cases are caused by anti-HPA-1a antibodies. In contrast, anti-HLA class I antibodies are rarely found in FNAIT, but are frequently implicated in cases of platelet transfusion refractoriness (PTR). This phenomenon leads to ongoing debate regarding the role of anti-HLA class I antibodies in FNAIT. In this study, we investigated the platelet clearance mediated by anti-HLA class I antibodies in whole blood both in vitro and in vivo.MethodsClearance of opsonized platelet was analyzed by platelet phagocytosis assay and by antibody administration to Balb/c female mice.ResultsTo mimic FNAIT conditions, whole blood was pretreated with anti-HLA antibodies before the phagocytosis of anti-HPA-1a antibody-opsonized platelets. Compared to untreated whole blood, anti-HLA-ABC and anti-HLA-DR IgG antibodies inhibited the phagocytosis of anti-HPA-1a-antibody-opsonized platelets. Similar results were obtained with purified monocytes, indicating that anti-HLA-ABC antibodies bound to monocytes can interfere with antibody-mediated platelet phagocytosis. Furthermore, the administration of anti-MHC-I antibodies to mice led to a significant decrease in the platelet count within 24 h. However, anti-αIIbβ3 antibody administration resulted in significantly higher platelet clearance over different time points. Analysis of antibody-bound platelets showed the presence of anti-αIIbβ3 antibodies on the platelet surface, but not on monocytes. In contrast, anti-MHC-I antibodies were found on both platelets and monocytes. Interestingly, monocytes exhibited higher levels of anti-MHC-I binding than platelets (87.0% vs. 25.5%), most likely because platelets express significantly fewer HLA class I antigens than monocytes, as indicated by our flow cytometric analysis of whole blood.ConclusionsThese results indicated that anti-MHC-I antibodies preferentially bind to monocytes rather than platelets in whole blood and can be cleared by monocytes via endocytosis. Furthermore, we found that the presence of anti-HLA class I antibodies did not significantly influence platelet clearance induced by anti-αIIbβ3 antibodies. The question of whether these observations can explain the controversial opinions regarding the relative roles of anti-HLA class I and anti-αIIbβ3 antibodies in FNAIT requires further assessment in a murine model of FNAIT.